Penerapan Business Intelligence Untuk Menganalisa Data Gempa Bumi di Indonesia Menggunakan Tableau Public - Diana Fitri Lessy; Arry Avorizano; Firman Noor Hasan (STMIK Budi Darma, 2022)
One of the natural disasters that often occurs in Indonesia is an earthquake. This is because Indonesia's geological position is between 3 important lithospheric plates, namely the Pacific, Eurasian and Indo-Australian plates. The forces between the plates are constantly changing, dampening disturbances both on land and at sea. This study aims to focus on visualizing earthquake data in Indonesia and implementing Business Intelligence to display earthquake area data, depth and magnitude. The method of this study uses the Tableau Public platform to process earthquake datasets in Indonesia obtained through www.kaggle.com for the period 01 January 2018 to 30 September 2022. This research produces a report in the form of a dashboard that contains data visualization for the earthquake area, depth and magnitude from various regions in Indonesia that can be used to assist in decisions to be taken. Various designs for dashboards can be used in Tableau to make data easier to read and understand.